Analytical Study of Bone Mineral Density (BMD) In Various Community of Navi Mumbai - Hande, Sudarshan (International Journal of Pharmaceutical & Biological Archive, 2016)
Osteoporosis, a condition characterized by decreased bone strength, is prevalent among post menopausal women but also occur in men & women with underlying conditions or major risk factors associated with bone demineralization. Low bone mineral density (BMD) is a major risk factor for osteoporosis and its related fractures. Fracture risk increases as bone mineral density declines. The most accurate test of bone density is dual-energy X-ray absorptiometry (DXA). The measurements, known as T-scores, determine which category - osteopenia, osteoporosis, or normal - a person falls into. Different communities may be expected who have a different lifestyle, such as different levels of activity and different eating habits. However, from clinical and public health point of view, it is important to verify BMD for determination of bone strength of various communities.